2014
DOI: 10.19261/cjm.2014.09(1).03
|View full text |Cite
|
Sign up to set email alerts
|

Activated Carbons from Vegetal Raw Materials to Solve Environmental Problems

Abstract: Abstract. Technologies for active carbons obtaining from vegetable byproducts such as straw, nut shells, fruit stones, sawdust, hydrolysis products of corn cobs and sunfl ower husks have been developed. The physico-chemical characteristics, structural parameters and sorption characteristics of obtained active carbons were determined. The ability of carbonaceous adsorbents for detoxifi cation of soil against pesticides, purifi cation of surface waters and for removal of organic pollutants from wastewaters has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…[19,20]. The morphological structure of these sources of raw matter favors the obtaining of specimens of activated carbon with high performance values [21] regarding adsorption capacity and increased mechanical resistance [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…[19,20]. The morphological structure of these sources of raw matter favors the obtaining of specimens of activated carbon with high performance values [21] regarding adsorption capacity and increased mechanical resistance [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…dqt/dt= K 1 (qe-qt) … (5). specific surface area exceeds 400 m 2 /g (Mukhin et al, 2014) but it is large compared to that found when the bones were calcined at 800 °C for 2 hours (72 m 2 /g) (Ghrab et al, 2017). While the surface of this adsorbent has a pore size is greater than 50nm which explains why the pores are large (macroporous), this is the expected result when using carbonization with chemical activation (Duca et al, 2018).…”
Section: Pseudo First-order Modelmentioning
confidence: 81%
“…Active carbons obtained by recycling annually renewable plant wastes (the straw of various oilseed brassica crops), represent a black powder [6][7][8][9][10][11]. Powdered activated carbons derived from rape, winter cress, mustard and radish straw according to the developed method (Tables 2, 3) (the product yield level is from 5,7% to 17,9%) have the following characteristics: А с -16,5% wt.…”
Section: Methodsmentioning
confidence: 99%